A intenção feminina de permanecer em um relacionamento abusivo - Gomes, Ingridd Raphaelle Rolim (2018)
Violence against women presents in its most varied types, and all of them have evidenced increasing data in Brazil and, in the State of Alagoas. Allied to this, it is possible to notice a portion of women who do not denounce their experiences of violence and, thus, researchers have become interested in the behavior of permanence in an abusive relationship. This study has the objective of understanding how the decision process of maintenance / abandonment of abusive relationship, based on the Theory of Planned Action, takes place, as well as to elaborate an instrument on the Female Behavior of being in an abusive relationship. The dissertation is composed of three chapters, corresponding to three articles. In the first article, studies were searched in Portuguese, English and / or Spanish in six databases. The results of this study reveal an inexpressive number of investigations and it seems to indicate that the applicability of this topic of study, from this theory, is still very scarce, although all studies refer to the nomological validity of this theoretical model. In the second article, individual semi-structured interviews were conducted with a sample of 27 women between the ages of 18 and 42. The results demonstrate the unfavorable attitudes of the interviewed women towards staying in abusive relationships, the perceived social pressure to perform this behavior reveals religion and the family as factors that can act both as protection and risk. And for perceived behavioral control, financial dependence, emotional dependence, and child protection were the main factors identified as obstacles to the exit of these relationships. The last study was carried out in two stages: (1) belief analysis for the construction of a quantitative instrument; and (2) application of this instrument. In the first stage, 27 university women participated and were conducted through semi-structured interviews and, in the second stage, 874 university women answered the questionnaire. The results demonstrate that the intention of women to remain in an abusive relationship is only associated with subjective norms, that is, perceived social pressure, indicating the influence of the culture of the patriarchy against this decision. The results of this dissertation are unpublished in Brazilian literature and may contribute to the contextualisation of more effective public policies in the face of this phenomenon.